O processo de construção de saberes docentes de professores de graduação tecnológica - Garcia, Airton de Oliveira (Universidade do Vale do Rio do Sinos, 2007)
The current piece of work aims, by means of an analysis of the professional education, understand the constructive process of the different sorts of teaching knowledge, in particular those related to Technological Graduation. In the abstract, there is search for relating the neoliberal policies for Educacion to the productive structure and the social contest of this new Course modality. Throughout a qualitative nature research; settings, actions and intentionalities present in teaching práxis of those who have been working in this sort of course were reconstructed. This piece of work involves the possible view of a researcher teacher who, while in pursuit of understanding which these different sorts of knowledge are, as from the interlocution of his partners, resignified places and actions by means of the speeches and silentness registered in the research instrument. The authors who supported the theoretical approach of this research are: Gramsci, Freire, Giroux, Nosella, Frigotto, Tardif, Nóvoa, Forrester
Keywords: avaliação; capacitação tecnólogica; educação profissional; ensino superior; formação; profissão; tecnologia; professor universitário; praxis teaching; technological graduation; knowledge; Ciências Humanas